Analysis of Learning Methods of The Great Children's Learning Institution (AHE) Pladen Unit in Pladen Village - Kurniawati, Nafisa Junita; Sa'diyah, Isnaini Khalimatus; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: This study aims to describe the history of the establishment and learning methods at the Les Baca AHE educational institution, Paden unit no. 1992. Research Methods: The method used in this study is descriptive qualitative. Data collection is in the form of interviews. In addition, the methods used include 6 steps, namely; brain gymnastics, remedial, reading modules, enrichment, writing, and games. Finding/Results: The results of the study indicate that the establishment of the Les Baca AHE educational institution is based on interest in developing children's reading skills in Pladen Village. In addition, the methods used include 6 steps, namely; brain gymnastics, remedial, reading modules, enrichment, writing, and games.